Effects of laser shock peening on SCC behavior of Alloy 600 in tetrathionate solution. (January 2015) - Telang, Abhishek; Gill, Amrinder S.; Teysseyre, Sebastien; Mannava, Seetha R.; Qian, Dong; Vasudevan, Vijay K.
Highlights: Deep compressive residual stresses were introduced after laser shock peening. Laser shock peening reduced the susceptibility to stress corrosion cracking. Longer time to failure in tetrathionate solution after laser shock peening. Improvement attributed to compressive residual stresses and microstructure. Abstract: In this study, the effects of laser shock peening (LSP) on stress corrosion cracking (SCC) behavior of nickel based Alloy 600 in tetrathionate solution were investigated. The LSP induced compressive residual stresses and changes in the near surface microstructure, hardness were characterized. The effects of LSP on SCC susceptibility of Alloy 600 in tetrathionate solution were evaluated by slow strain rate tests and constant load tests. The results indicate a significantly longer time to failure and decreased susceptibility to SCC. These improvements were attributed to LSP induced compressive residual stresses, increased yield strength and hardening caused by near-surface microstructural changes.